Implementation of Lesson Study Program Through The PJBL Model To Improve The Quality Of Learning Media Products for Primary School Created by Pre-Service Primary Education Teacher - Endang Herawan; Dede Trie Kurniawan; Sri Maryanti (JETL (Journal of Education, Teaching and Learning), 2022)
This elementary school learning media development program aims to provide a picture of improving the quality of learning media product creation for prospective elementary teacher students after carrying out lesson study activities based on the Lecturer Expertise area in the PGSD FKIP Unswagati Cirebon study program. The research method uses descriptive methods. The study population was second-year students prospective teachers of the FKIP Unswagati Elementary School in Cirebon. The expectation of this program is an increase in the ability of lecturers to plan lectures to improve better, the ability of lecturers to implement lectures is expected to be even better. Through this program Lecturers are expected to be able to create a more interesting lecture process. Can make students more active and creative in exploring to produce elementary school learning products that are creative, innovative and fun. This program encourages lecturers to have a well-organized learning structure. Teaching skills such as mastery of the material, use of lecturing media, classroom management, questioning skills and motivating skills of students are trained in this program through the principle of collegiality. Lesson study activities have the potential to increase lecturer professionalism which has an impact on improving the quality of the process and results of lectures. The results obtained from this study were an increase in the quality of lectures conducted by collegial learning based on collegiality of lecturers' colleagues in teaching which was facilitated in the lesson study program.